Acute caffeine mouth rinsing does not improve 10-km running performance in CYP1A2 C-allele carriers - Figueiredo, Nayra; Queiroz, Marcela; Felicio, Fernanda P.; Ferreira, Jessica; Gerosa-Neto, Jose [UNESP]; Mota, Jo Ao F.; Silva, Christielly R. da; Ghedini, Paulo C.; Saunders, Bryan; Pimentel, Gustavo D. (Elsevier B.V., 2021)
Purpose: This study assessed whether caffeine mouth rinsing affects 10-km run performance and vertical jump in recreational runners. Methods: A double-blind, placebo-controlled, crossover study was conducted. Ten well-trained volunteers performed two trials, following caffeine or placebo mouth rinse, separated by seven days. Immediately before the 10-km run, a 10-second mouth rinse with either 300 mg of caffeine (1.2%) or microcrystalline cellulose (placebo) diluted in 25 mL of water was performed. Pre- and post-exercise, participants performed a vertical jump test. A Garmin Forerunner (R) GPS, was used to measure 10-km running time and an 11-point Borg scale was used post-exercise to measure ratings of perceived exertion. Blood samples were also collected during the visit in the laboratory in the afternoon period to classify individuals according to their CYP1A2 genotype. Vertical jump performance was evaluated using a force plate. Results: Nine runners (90%) were CC homozygotes and one (10%) was an AC heterozygote for CYP1A2. There was no difference in 10-km time-trial performance (Placebo: 47.07 +/- 5.18 vs. CAF: 47.45 +/- 6.34 min, p = 0.89), ratings of perceived exertion (Placebo: 17 +/- 1 vs. CAF: 16 +/- 2, p = 0.34) or vertical jump power (Placebo, Pre: 4.5 +/- 0.6 W.kg-1 and Post: 4.5 +/- 0.7 W.kg-1; CAF: Pre: 4.4 +/- 0.7 W.kg-1 and Post: 4.4 +/- 0.8 W.kg-1, d = 0.21, p = 0.66) between trials. Conclusion: Acute caffeine mouth rinsing (1.2%) did not improve 10-km performance and showed similar null effects on vertical jump performance in CYP1A2 C-allele carriers. (C) 2021 European Society for Clinical Nutrition and Metabolism. Published by Elsevier Ltd. All rights reserved.
Keywords: Caffeine; CYP1A2; Mouth rinse; Running; Genotype; Ergogenic aid